Site index curves in eucalyptus plantation obtained by quantile regression - Araújo Júnior, Carlos Alberto; Soares, Carlos Pedro Boechat; Leite, Helio Garcia (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to obtain site index curves in eucalyptus plantations by quantile regression, and to compare them to the obtained ones with the use of fitted regressions by the method of ordinary least squares. Quantile regression can be used to generate site index curves, especially in the presence of outliers. The method generates a bundle of curves better adjusted to the observed data, compared to the one generated with the estimates of ordinary least squares, either by the guide curve method (anamorphic curves) or by polymorphic curves (using different percentiles).